2021
DOI: 10.1038/s41598-021-93221-9
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-first-century projections of shoreline change along inlet-interrupted coastlines

Abstract: Sandy coastlines adjacent to tidal inlets are highly dynamic and widespread landforms, where large changes are expected due to climatic and anthropogenic influences. To adequately assess these important changes, both oceanic (e.g., sea-level rise) and terrestrial (e.g., fluvial sediment supply) processes that govern the local sediment budget must be considered. Here, we present novel projections of shoreline change adjacent to 41 tidal inlets around the world, using a probabilistic, reduced complexity, system-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 46 publications
1
29
1
Order By: Relevance
“…Considering that the coastline will change because of natural factors, such as sedimentation, seawater erosion, global warming, and human-made factors (e.g., port construction, land reclamation, and marine engineering) [20,49,50], the coastline at different periods also may change. Great changes likely will occur.…”
Section: Consistency Comparison Between Coastline Extraction Results and Other Data Productsmentioning
confidence: 99%
“…Considering that the coastline will change because of natural factors, such as sedimentation, seawater erosion, global warming, and human-made factors (e.g., port construction, land reclamation, and marine engineering) [20,49,50], the coastline at different periods also may change. Great changes likely will occur.…”
Section: Consistency Comparison Between Coastline Extraction Results and Other Data Productsmentioning
confidence: 99%
“…The general behaviour of STIs is a function of fluvial processes (e.g., fluvial sediment fluxes) and oceanic processes [e.g., wave driven longshore sediment transport (LST)], all of which are projected to change as a result of climate change (Ranasinghe et al, 2013;Duong et al, 2016). Several studies over the last decade or so have shown that climate change will lead to multiple impacts in STI environs, including a decrease in inlet stability, erosion of inlet-adjacent coasts, erosion of estuary margin shorelines, permanent or frequent inundation of low lying areas along estuary margins, estuarine eutrophication, and toxic algal blooms (Duong et al, 2017(Duong et al, , 2018Bamunawala et al, 2020aBamunawala et al, ,b, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Changes to the inlet or the adjacent coast could therefore impact some or all of these human activities, leading to substantial socio-economic losses, and in some situations, threaten the safety of coastal communities 8 10 . Several recent studies have shown that, due to climate change, such system changes are all but inevitable over the twenty-first century 13 , 14 , and effective adaptation strategies therefore need to be developed and implemented. To properly inform such adaptation strategies, long term (~ 50–100 years) projections of how inlets may change in future, including quantification of the uncertainty associated in these projections, are required.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike uninterrupted coasts that are governed only by oceanic processes such as tides, waves and mean sea level (MSL), inlet-interrupted coasts are also governed by terrestrial processes such as riverflow and fluvial sediment 6 , 8 10 , 14 18 . Therefore, projected climate change driven variations in any of these drivers can lead to many negative physical impacts on inlet-interrupted coasts, such as shoreline retreat adjacent to the inlet, erosion of estuary margin shorelines, inundation of low lying areas along estuary margins, estuarine eutrophication, and toxic algal blooms etc 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation